A preliminary investigation on CO-simulation-emulation environment for study healthcare network - Ong H.S.; Chow P.K. (2023)
The implementation of digital radiology in modern hospital poses great challenge to network designers. They have to come up with a communication infrastructure in the healthcare environment that could handle heavy bursty traffic with high volume of digital image files transfer. Currently, the design of a hospital network with digital radiology is mainly based on enterprise network design. A repeated what-if experimentation of the network design before implementation is worthwhile to avoid costly after implementation correction. This paper presents a preliminary study on the notion of co-simulation-emulation of digital radiology experimentation in a hybrid testbed of simulation, emulation and live network solution. The behaviour of a healthcare network was studied and the feasibility such system is reported.